Pelatihan manajemen emosi pada siswa SMA di Makassar - Ahmad Ahmad (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This activity aims to 1) knowing students' responses to emotional management training. 2) improve emotional management skills for students. Participants were 40 students of SMAN 14 Makassar selected purposive sampling. The results of this activity are improve the emotional management competence of students of SMAN 14 Makassar.